Crusted Scabies pada Remaja dengan Reaksi Lepra Tipe-2 Steroid-Dependent - Limyanti Dwi Vicaria (Cermin Dunia Kedokteran, 2024)
Introduction Crusted scabies is more often found in immunocompromised conditions. This disease is also associated with various problems, such as delayed diagnosis, secondary infection, and mortality due to sepsis. Case A 17-year-old boy with itching and scaly skin between fingers and toes for one month. Antifungal therapy resulted in no improvement. The patient has had a history of leprosy reactions when treated with steroids since 2019. Crusted lesions were covered with extensive scales and thick hyperkeratosis between the fingers and toes. There is also leucocytosis. The clinical diagnosis was crusted scabies with a secondary infection. Patient was given clindamycin, cetirizine, 0.9% NaCl compresses, coconut oil, and 5% permethrin. On day 14, lesions improved.